Rationally designed hecogenin thiosemicarbazone analogs as novel MEK inhibitors for the control of breast malignancies. Issue 24 (15th December 2017) - Elsayed, Heba E.; Ebrahim, Hassan Y.; Haggag, Eman G.; Kamal, Amel M.; El Sayed, Khalid A.
Graphical abstract: Abstract: Natural products have documented oncology success history as valuable scaffolds for selective target modulation. Herein, the sapogenin hecogenin (1 ) was screened for its anti-breast cancer inhibitory capacity using in vitro assays, including proliferation, cytotoxicity, migration, invasion assays, and Western blotting. The results identified1 as a propitious hit with modest activities attributed to the concurrent down-regulation of mitogen activated protein kinase kinase/extracellular signal-regulated kinase (MEK) distinctive downstream effectors. Guided by in silico 3D-structural insights of MAPK kinase domain, an extension strategy was adopted at1 's C-3 and C-12 aimed at the design of novel hecogenin-based analogs with improved target binding affinity. Thirty-three analogs were prepared and tested, among which hecogenin 12-(3′-methylphenyl thiosemicarbazone) (30 ) displayed the most potent selective anticancer effects. Analog30 demonstrated antiproliferative, antimigratory and anti-invasive activities at low μM level, compared to the negligible effect on the non-tumorigenic MCF-10A mammary epithelial cells. Durable regression of breast tumor xenografts in athymic nude mice was observed after treatments with30, compared to its parent hecogenin at the same dose regimen, confirmed the hit-to-lead promotion of this analog. Hecogenin-12-thiosemicarbazones, represented by30, is a novel MEK inhibitory lead class to control breast neoplasms.